Pengetahuan Pantang Makan pada Ibu Pospartum di Kabupaten Tanah Laut Provinsi Kalimantan Selatan - Ayu, Putri; Hipni, Rubiati (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2020)
Background : Indonesian Demographic and Health Survey (IDHS) in 2013, the maternal mortality rate (MMR) reached 359 per 100,000 live births. During the puerperium diet problems need to get serious attention, because with good nutrition can accelerate the healing of the mother and greatly affect the composition of milk The impact that occurs in postpartum mothers who abstain from food, nutritional needs will be reduced. Based on a preliminary study on 8-11 May 2019, the average monthly visit was 30 postpartum mothers, after interviews with postpartum mothers in the Panyipatan Community Health Center work area, there were 10 postpartum mothers, with initial data 8 of which did not know about abstinence and 2 some of them understand. Objective: To determine the level of knowledge of Nifas about abstinence during the puerperium at Panyipatan health center, Panyipatan sub-district, Tanah Laut regency in 2019 at a level of good, adequate and insufficient. Research Methods: The design of this study used a quantitative descriptive design. This research was conducted at Panyipatan Health Center, Panyipatan Subdistrict, Tanah Laut Regency. The sample in this study were 30 postpartum mothers. The instrument of this research is a questionnaire. The method of collecting data comes from primary data and secondary data. The single variable is the level of knowledge of Nifas about abstinence during puerperium. The analysis uses univariate and bivariate analysis with a percentage formula. Research Results: The level of knowledge of postpartum mothers about abstinence during the puerperium at Panyipatan Health Center, Panyipatan Subdistrict, Tanah Laut Regency in 2019, respondents with a good level of knowledge were 4 respondents (14%), sufficient knowledge level was 11 respondents (36%) and knowledge level less than 15 respondents (50.0%). Conclusion: Mother Nifas's level of knowledge about abstinence during puerperium at Panyipatan health center, Panyipatan sub-district, Tanah Laut regency in 2019 at a level of insufficient knowledge.